2021
DOI: 10.20892/j.issn.2095-3941.2020.0389
|View full text |Cite
|
Sign up to set email alerts
|

FGFR/RACK1 interacts with MDM2, promotes P53 degradation, and inhibits cell senescence in lung squamous cell carcinoma

Abstract: Objective: FGFR is considered an important driver gene of lung squamous cell carcinoma (LSCC). Thus, identification of the biological events downstream of FGFR is important for the treatment of this malignancy. Our previous study has shown that the FGFR/RACK1 complex interacts with PKM2 and consequently promotes glycolysis in LSCC cells. However, the biological functions of the FGFR/RACK1 complex remain poorly understood. Methods: Anchorage-independent assays and in vivo tumorigenesis assays were performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…demonstrated that LRP1 was upregulated at the transcriptional level and protein level through direct promoter binding by p53 and p53-activating stresses ( 53 ). Based on previous work confirming the role of MIF in stabilizing the binding of p53-Mdm2, leading to suppression of p53 activity in apoptosis and cell cycle arrest, it is reasonable to presume that the elevated mRNA expression of LRP1 in MIF knockdown cells in the present study might result from MIF-induced inhibition of p53 activity ( 54 , 81 83 ). More rigorous studies are needed to address this regulatory mechanism.…”
Section: Discussionsupporting
confidence: 66%
“…demonstrated that LRP1 was upregulated at the transcriptional level and protein level through direct promoter binding by p53 and p53-activating stresses ( 53 ). Based on previous work confirming the role of MIF in stabilizing the binding of p53-Mdm2, leading to suppression of p53 activity in apoptosis and cell cycle arrest, it is reasonable to presume that the elevated mRNA expression of LRP1 in MIF knockdown cells in the present study might result from MIF-induced inhibition of p53 activity ( 54 , 81 83 ). More rigorous studies are needed to address this regulatory mechanism.…”
Section: Discussionsupporting
confidence: 66%
“…The tumor suppressor gene P53 is involved in cell cycle control, apoptosis, and genomic stability, and P53 mutations appear in many cancers. The dysregulated expression or function of pRB or P53 is a hallmark of all cancers 37 . Although P53 is one of the most well-studied genes, its role in adipocytes remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The p53-p21 axis is a key signaling pathway activated at the onset of senescence 7 . Although p53 is not required to initiate the SASP, it can either promote secretion of several factors or restrain the SASP.…”
Section: Potential Role Of Eif5a In Translational Control Of the Saspmentioning
confidence: 99%